Geologi dan Potensi Terbentuknya Mineralisasi Uranium di Daerah Harau, Sumatera Barat - Ngadenin, Ngadenin (BRIN Publishing, 2013)
The Background of this study is due to the geological setting of Harau area and its surrounding, West Sumatera, that is identified as a favourable area for uranium accumulation which is indicated by the presence of anomalous radioactivity in the Tertiary sedimentary rocks deposited on the terrestrial environment and the presence of anomalous uranium contents in Pre-Tertiary granites in several places in West Sumatera, and the presence of radioactivity anomalous in the Pre Tertiary metamorphic rocks. The purpose of this study is to determine the potential formation of uranium mineralization in the Harau area, to be used as a basis to conduct more detailed research in order to inventory the potential of uranium resources in Indonesia. The scope of the discussion in this review includes a discussion of geology, geochemistry and radioactivity of the outcrops. The composition of regional stratigraphic from old to young is quartzite unit, phyllite unit, conglomerate unit, sandstone unit, tuff unit and alluvium river. The main fault that developed in the study area are normal faults trending southwest – northeast. The study area is splitted into two sections where the southeastern part relatives fall down of the northwest. Based on geological setting, radioactivity and uranium data then is assumed that Harau is a potential area for the formation of uranium mineralization in sandstone and its vein type. Sandstone type is expected occur in sandstone conglomerate unit of The Brani Formation and vein type is expected occur in the quartzite unit of The Kuantan Formation.